Obtenção de rutina ricinoleato através da reação de esterificação com óleo de mamona - Ribeiro, Fernanda Pinheiro de Carvalho (2016)
The flavonoid rutin (3-0-rutinosídeo-quercetin) stands out among the natural products as a promising alternative in the fight against degenerative diseases and related to aging. However, the low solubility and stability thereof in different media, especially lipophilic limited applications in pharmaceutical preparations. The biocatalytic transformation by enzymatic acylation has been suggested by several authors, with good reaction yields. In this sense, the objective of this study was to promote the enzymatic acylation of rutin, using castor oil as acylating agent and lipase as a catalyst, to characterize the formed product, estimate the efficiency of bioconversion, and to investigate in vitro the antioxidant activity and cytotoxic effect opposite the reaction product Vero cells. The catalytic transformation occurred at 50ºC for 120 hours. The product was subjected to column chromatography, followed by filtration by Sephadex LH-20. The chemical structure of rutin-O-ricinoleate was determined by Nuclear Magnetic Resonance (NMR) 1H and 13C and by liquid chromatography / mass spectroscopy (HPLC/MS). In another experiment, it was observed the formation of the ester content by High Performance Liquid Chromatography coupled to a detector diode arrangements (HPLC-DAD) under conditions which allow assessing the reaction yield over 120 hours. The analytical method proposed has been validated considering the linearity parameters, accuracy, precision, limit of quantification and detection proved to be suitable for quantification of ricinoleato rutin. It was found by this method that the reaction product maintained the antioxidant capacity of rutin and there was no evidence of cytotoxicity.